(untitled) (Studia Prawnicze / The Legal Studies, 2023)
It is in the broad sphere of human rights that the author wants to posit prisoner’s rights. In order to make progress in this respects it is necessary to overcome complexes and prejudices that exist in the society, then — to furnish the prisoners with legal instruments and ensure their efficient operation by, first of all, fully accessible, broad, judicial supervision. In the United States the common law system prevails, and accordingly, for the last ten years prisoner’s complaints arising in connection with the lack of observance of the clause — due process of law — have become the grounds for rulings of state and federal courts, the Supreme Court included. The clause has been embodied into the amendments V and XIV to the constitution, and reads: “No person shall be deprived of life, liberty or property, without due process of law.” It relates to almost all domains of law, and is a powerful instrument of the protection of human rights. Therefore, in the discussed sphere — due to conflicting interests, trends and opinions — the clause makes the society aware of the wrongs done to individuals, misused authority, the mistakes of the penal system itself. The author has devided the material under analysis into three parts: the first one embraces the classification of prisoners and covers the problem of their transfer to other penal establishments, the second — deals with disciplinary procedures, the third one — dwells upon the problems arising in connection with parole. In the final part of the article the author presents a great variety of facts in prisoner’s life where the clause can lie, moreover, he stresses that prisoners bring actions to court on the grouds of other constitutional clauses. Although the analysed material does not provide a general outlook into the legal situation of prisoner in the United States, it satisfactorily characterizes the progress that is labourously being made in the sphere. Moreover, it reflects a universal truth that even ideally formulated provisions of law, slogans and declarations can remain of no significance for persons concerned, whereas under certain circumstances, even enigmatically worded, archaic formula can contribute to effective progress.